2011
DOI: 10.1016/j.reseneeco.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of responses to single and repeated discrete choice questions

Abstract: According to neoclassical economic theory, a stated preference elicitation format comprising a single binary choice between the status quo and one alternative is incentive compatible under certain conditions. Formats typically used in choice experiments comprising a sequence of discrete choice questions do not hold this property.In this paper, the effect on stated preferences of expanding the number of binary choice tasks per respondent from one to four is tested using a split sample treatment in an attribute-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 47 publications
3
40
2
Order By: Relevance
“…However, all non-dictatorial mechanisms except a single binary choice format are generically incentive incompatible (Gibbard 1973;Satterthwaite 1975). Both mechanism design theory (Hurwicz 1960) and empirical evidence (Bateman et al 2008;Day et al 2011;McNair et al 2011) suggest that repeated choice tasks per respondent induce strategic behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, all non-dictatorial mechanisms except a single binary choice format are generically incentive incompatible (Gibbard 1973;Satterthwaite 1975). Both mechanism design theory (Hurwicz 1960) and empirical evidence (Bateman et al 2008;Day et al 2011;McNair et al 2011) suggest that repeated choice tasks per respondent induce strategic behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Other papers have also concluded that the data are consistent with respondents using previously encountered information and past choices and that estimated parameters are sensitive to how choice sets are ordered. Strategic behaviour in respondents, particularly the weaker version of strategic behaviour, is not rejected (Scheufele and Bennett 2010a;2010b;McNair et al, 2011a).…”
Section: Heuristics Of Choice Set Inter-dependencementioning
confidence: 99%
“…Value learning involves the discovery of preferences and taste parameters may change according to the attribute levels presented to the respondent. Hence, preferences can be influenced by the starting point and subsequent attribute values (McNair et al, 2011a), with the 'good-deal / bad-deal' heuristic being a specific case in point. It is possible that in a group of respondents, decision process heterogeneity involving several heuristics are at work and no one heuristic dominates.…”
Section: Heuristics Of Choice Set Inter-dependencementioning
confidence: 99%
See 1 more Smart Citation
“…In these types of surveys, the set of options from which the respondent chooses is referred to as the "choice set." Although most multinomial-choice surveys utilize "repeated choice," wherein each individual respondent evaluates multiple choice sets, we wished to avoid any of the confounding effects associated with this approach and presented each respondent with exactly one choice set to evaluate (Bateman et al 2001(Bateman et al , 2004Day et al 2012;Day and Prades 2010;DeShazo 2002;Holmes and Boyle 2005;Krosnick 1999;Ladenburg and Olsen 2008;and McNair, Bennett, and Hensher 2011). This also facilitates comparison with the results of the binary-choice version.…”
Section: Survey Design and Administrationmentioning
confidence: 99%